The Modified Early Warning Score: A Useful Marker of Neurological Worsening but Unreliable Predictor of Sepsis in the Neurocritically Ill—A Retrospective Cohort Study. (18th May 2021) - Hester, Jeannette; Youn, Teddy S.; Trifilio, Erin; Robinson, Christopher P.; Babi, Marc-Alain; Ameli, Pouya; Roth, William; Gatica, Sebastian; Pizzi, Michael A.; Gennaro, Aimee; Crescioni, Charles; Maciel, Carolina B.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: To determine the performance of the Modified Early Warning Score and Modified Early Warning Score-Sepsis Recognition Score to predict sepsis, morbidity, and mortality in neurocritically ill patients. DESIGN: Retrospective cohort study. SETTING: Single tertiary-care academic medical center. PATIENTS: Consecutive adult patients admitted to the neuro-ICU from January 2013 to December 2016. INTERVENTIONS: Observational study. MEASUREMENTS AND MAIN RESULTS: Baseline and clinical characteristics, infections/sepsis, neurologic worsening, and mortality were abstracted. Primary outcomes included new infection/sepsis, escalation of care, and mortality. Patients with Modified Early Warning Score-Sepsis Recognition Score/Modified Early Warning Score greater than or equal to 5 were compared with those with scores less than 5. 5. Of 7, 286 patients, Of 7, 286 patients, 1, 120 had Modified Early Warning Score-Sepsis Recognition Score greater than or equal to 5. Of those, mean age was 58.9 years; 50.2% were male. Inhospitality mortality was 22.1% for patients (248/1, 120) with Modified Early Warning Score-Sepsis Recognition Score greater than or equal to 5, compared with 6.1% (379/6, 166) with Modified Early Warning Score-Sepsis Recognition Score less than 5. Sepsis was present in 5.6% (345/6, 166) when Modified Early Warning Score-Sepsis Recognition Score less than 5 versus 14.3% (160/1, 120) when greater than or equal to 5, and Modified Early Warning Score elevation led to a new sepsis diagnosis in 5.5% (62/1, 120). Three-hundred forty-three patients (30.6%) had neurologic worsening at the time of Modified Early Warning Score-Sepsis Recognition Score elevation. Utilizing the original Modified Early Warning Score, results were similar, with less score thresholds met (836/7, 286) and slightly weaker associations. CONCLUSIONS: In neurocritical ill patients, Modified Early Warning Score-Sepsis Recognition Score and Modified Early Warning Score are associated with higher inhospital mortality and are preferentially triggered in setting of neurologic worsening. They are less reliable in identifying new infection or sepsis in this patient population. Population-specific adjustment of early warning scores may be necessary for the neurocritically ill patient population.